Penerimaan Tarif Parkir Dampaknya Terhadap Net Income PT SPI Area Graha Rekso Jakarta - muchtar, ellyta (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2017)
Abstract. Revenue from the activity or activities of a company said revenue and earnings from the company related to the company's net profit. PT SPI is a company engaged in the service area management parkir.Purpose  this study to determine the revenue impact parking rates on net income of the company. The research data used is secondary data, the existing data on the income statement of PT SPI from the period 2011 to 2015. The research method used is quantitative descriptive data processing using SPSS data processing applications. The results showed that acceptance parking rates take effect or influence on the company's net income amounted to 97% (R square 0.97) with significant 0.002. 0.002 meaning <0,005. The regression equation established in the researh is Y = -0.709 + 1,014X + e . So that can concluded that this study has proven where the acceptance of the company's activities that have been carried out in the form of income parking rates have a relationship with the net profit or net income of the company. Keyword: Parking rate revenue , Net Income